ANALISIS KINERJA ORGANISASI DI DINAS SOSIAL, TENAGA KERJA, DAN TRANSMIGRASI KABUPATEN SEMARANG (STUDI KASUS PADA BIDANG SOSIAL PELAYANAN BANTUAN DAN JAMINAN SOSIAL TERHADAP PENYANDANG MASALAH KESEJAHTERAAN SOSIAL) - Rachmawati, Theodora Ratih; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
In addressing issues of social welfare, the Government and Local Government can provide assistance and social security as an embodiment of the implementation of the obligations of the state in securing the rights to the basic needs of citizens are poor and can not afford. The study will analyze the performance conducted by the Semarang District Social Service and the factors that drive and impede performance in the Semarang District Social Service assistance services and social security to social welfare issues (POM). This study uses the theory of organization and five dimensions of performance that productivity, the orientation of the quality of service, responsiveness, responsibility, and accountability with a qualitative descriptive approach. Data collection techniques used through observation, interviews, documentation and literature study with the informant Semarang District Social Service employee. The results showed that the performance is done Semarang District Social Service less than optimal because it is still a barrier such as issues of human resources, facilities and infrastructure is not sufficient enough, the limited budgetary funds to community participation is minimal. There needs to penyelenggarakan education, training and skills, and increases the number of HR from recruitment of civil servants or increase the number of temporary employees, proposed adding the amount of the budget in accordance with the needs required at the district budget Semarang, procurement of equipment and facilities, to disseminate to PMKSs with skills training, as well as improving coordination with the public and business community in supporting the program of advisory services and social security.